Counselling within Inuit Systems in Canada’s North - Brooker, Anya L. (Canadian Journal of Counselling and Psychotherapy, 2018)
This article discusses the history of Inuit culture with a focus on the intergenerational trauma that stemmed from colonialism, forced assimilation, and the Canadian government’s sovereignty efforts. This article addresses the loss of cultural identity among Inuit people that resulted from these events. A comparative statistical analysis between Northern and Southern Canada reveals the higher rates of psychosocial issues such as drug and alcohol abuse and family violence in Nunavut. Inuit culture is in a state of cultural transition and consequently requires culturally sensitive and knowledgeable counsellors. The author combines existing literature and personal observations from working as a clinician in Nunavut to arrive at recommendations for practice. The interventions of a family system’s therapy approach align well with Inuit values and will be discussed as one beneficial intervention for use with Inuit clients.